Carly DiFraia: capstone - DiFraia, Carly, artist (Colorado State University. Libraries, 2024)
The artist's statement: My approach to design is heavily influenced by my background in painting. I strive to merge the objectivity of design with the subjectivity of fine art. This duality pushes me to explore and question the established "rules" and parameters imposed by design. Through my skepticism of these norms, I aim to create work that not only meets functional design needs but also pushes outside of those boundaries. I also recognize the significance of design history and its relationship to our contemporary context, understanding that design is a mirror reflecting where we are positioned within that history. This also informs my creative process, which always begins with traditional tools—paper and pencil. This initial process helps me to think beyond the constraints of the digital realm, in order to have a deeper understanding of how design interacts in physical spaces.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design